Data and Mobility Transforming Information into Intelligent Traffic and Transportation Services. Proceedings of the Lakeside Conference 2010 - Düh, Julia; Hufnagl, Hartwig; Juritsch, Erhard; Pfliegl, Reinhard; Schimany, Helmut-Klaus; Schönegger, Hans (Advances in Intelligent and Soft Computing,, 2010)
This volume of Advances in Soft Computing contains the accepted and outstanding papers presented at the Lakeside Conference 2010 in Carinthia, Austria. The topic of the Lakeside Conference 2010, Data and Mobility - Transporting Information into Intelligent Traffic and Transportation Services, was chosen to underline the importance of information and mobility in transport and to discuss current activities in this sector. The development of traffic management systems, under the influence of new technologies, is a fast-changing subject and needs experts to guide us in the right direction. Worldwide, a variety of solutions is being developed to make traffic management safer, more sustainable and efficient. The 18 papers published in this book represent the work of national and international companies, universities and research & development departments and reflect a number of current research streams. The articles cover significant recent developments in the field, both in terms of data and mobility, self-learning traffic monitoring systems, ETC-based traffic telematics solutions and naturalistic driving - a new method of data collection. The wide range of activities also contains reports offering viewpoints on cross-border issues such as transnational nowcasting systems or the comparison between the European and the American ITS system architecture. The organizers also took special care to include papers dealing with national and geographical characteristics, such as the standardized documentation of flood damage and winter maintenance management systems.